NATURAL DELIVERY IN WOMEN WITH A SCAR ON THE UTERUS - Софья Сергеевна Синицына; Елена Николаевна Кравченко; Галина Федоровна Рублева; Марина Павловна Владимирова; Лариса Владимировна Куклина (The Publishing House Medicine and Enlightenment, 2018)
The number of women with a scar on the uterus is progressively increasing every year. The study of the course and outcome of labor in women with a scar on the uterus after a cesarean section, conservative myomectomy and uterine perforation will allow a careful selection of women for labor through natural birth canals. The aim of the research - to analyze the course of pregnancy and childbirth in patients with operated uterus after cesarean section, conservative myomectomy and uterine perforation. Material and methods. A retrospective analysis of 2589 births in women with a scar on the uterus occurred in the perinatal center in three years (2014-2016). Results. Analysis of the clinical material showed that of the 406 patients selected for delivery through the natural birth canal, 76.3 % were genetically conserved. Weakness of labor activity developed in 19.2 % of cases, fetal hypoxia - in 4.4 %, which was the reason of operative delivery. With full term pregnancy and the mature cervix of the uterus, in patients with scar on the uterus, induction of labor with the help of amniotomy is possible. The degree of maturity of the cervix is more likely to indicate the consistency of the scar on the uterus. Conclusion. Rational management of pregnant women with a scar on the uterus, the correct choice of the method and term of delivery allow to reduce the risk of obstetric and perinatal pathology.